Towards Point-of-Care Diagnostic and Staging Tools for Human African Trypanosomiaisis - Enock Matovu; Anne Juliet Kazibwe; Claire Mack Mugasa; Joseph Mathu Ndungu; Zablon Kithingi Njiru (Journal of Tropical Medicine)
Human African trypanosomiasis is a debilitating disease prevalent in rural sub-Saharan Africa. Control of this disease almost exclusively relies on chemotherapy that should be driven by accurate diagnosis, given the unacceptable toxicity of the few available drugs. Unfortunately, the available diagnostics are characterised by low sensitivities due to the inherent low parasitaemia in natural infections. Demonstration of the trypanosomes in body fluids, which is a prerequisite before treatment, often follows complex algorithms. In this paper, we review the available diagnostics and explore recent advances towards development of novel point-of-care diagnostic tests.